Accessing the diffracted wavefield by coherent subtraction - Schwarz, B; Gajewski, D (Oxford University Press, 2017)
Diffractions have unique properties which are still rarely exploited in common practice. Aside from containing sub-wavelength information on the scattering geometry or indicating small-scale structural complexity, they provide superior illumination compared to reflections. While diffraction occurs arguably on all scales and in most realistic media, the respective signatures typically have low amplitudes and are likely to be masked by more prominent wavefield components. It has been widely observed that automated stacking acts as a directional filter favoring the most coherent arrivals. In contrast to other works, which commonly aim at steering the summation operator towards fainter contributions, we utilize this directional selection to coherently approximate the most dominant arrivals and subtract them from the data. Supported by additional filter functions which can be derived from wavefront attributes gained during the stacking procedure, this strategy allows for a fully data-driven recovery of the faint diffracted background wavefield and makes it accessible for further processing. Large source-receiver offset acquisition offers the benefits of high data redundancy and improved illumination. However, large-offset recordings are generally expensive to acquire and the majority of academic research is confronted with a comparably low channel count and target depths that significantly exceed the available offset range. A complex single-channel field data example recorded in the Aegean sea near Santorini illustrates that the diffracted background wavefield is surprisingly rich and despite the absence of a high channel count can still be detected and characterized, suggesting a variety of applications in industry and academia.